Determination of cadmium at ultra-trace levels by CPE-molecular fluorescence combined methodology - Talio, María Carolina (2009)
A highly sensitive micelle-mediated extraction methodology for the preconcentration and determination of trace levels of cadmium by molecular fluorescence has been developed. Metal was complexed with o-phenanthroline (o-phen) and eosin (eo) at pH 7.6 in buffer Tris medium and quantitatively extracted into a small volume of surfactant-rich phase of PONPE 7.5 after centrifugating. The chemical variables affecting cloud point extraction (CPE) were evaluated and optimized. The RSD for six replicates of cadmium determinations at 0.84 μg L-1 level was 1.17%. The linearity range using the preconcentration system was between 2.79 × 10-3 μg L-1 and 2.81 μg L-1 with a correlation coefficient of 0.99. Under the optimal conditions, it obtained a LOD of 8.38 × 10-4 μg L-1 and LOQ of 2.79 × 10-3 μg L-1. The method presented good sensitivity and selectivity and was applied to the determination of trace amounts of cadmium in commercially bottled mineral water, tap water and water well samples with satisfactory results. The proposed method is an innovative application of CPE-luminescence to metal analysis comparable in sensitivity and accuracy with atomic spectroscopies.